2008
DOI: 10.1111/j.1365-2141.2008.07046.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutated and non‐mutated TP53 as targets in the treatment of leukaemia

Abstract: SummaryTP53 is mutated in 10-20% of cases of chronic lymphocytic leukaemia (CLL) and 3-8% of cases of acute myeloid leukaemia (AML). Recently, two classes of compounds that restore the function of p53 in tumours have been described. PRIMA-1 (p53-dependent reactivation and induction of massive apoptosis) restores the wild-type conformation of mutant TP53, whereas RITA (reactivation of p53 and induction of tumour cell apoptosis) increases intracellular levels of p53. We evaluated the effects of RITA alone and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…Increased levels of p53 in response to RITA correlated with the induction of apoptosis reported earlier (31). Activation of the p53 apoptotic pathway in MM cells was further documented by the upregulation of NOXA and GADD45A, which was confirmed and verified by microarray and qRT-PCR.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Increased levels of p53 in response to RITA correlated with the induction of apoptosis reported earlier (31). Activation of the p53 apoptotic pathway in MM cells was further documented by the upregulation of NOXA and GADD45A, which was confirmed and verified by microarray and qRT-PCR.…”
Section: Discussionsupporting
confidence: 78%
“…RITA has been shown to have efficacy in various solid tumors such as colon, breast, cervical, and lung carcinoma, osteosarcoma, and renal cell carcinoma (20,(26)(27)(28)(29)(30). There has been only one report describing antileukemic activity of RITA in acute myelogenous leukemia and chronic lymphocytic leukemia, which was limited to the study of the expression of p53 only (31). The role of RITA in MM has not been addressed, and little is known about the downstream effectors of the p53/MDM2 pathway in response to RITA in hematologic malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…39 Furthermore, the latest results of research showed improvement in the in vitro drug chemosensitivity in p53-deleted cells after coincubation of RITA (reactivation of p53 and induction of tumor cell apoptosis) and PRIMA-1. 40 …”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Surprisingly, in contrast to solid tumors, hematologic malignancies present a rather low incidence of genetic alterations in TP53 (10%-20%). 37,38 TP53 mutations/deletions have been reported in chronic lymphocytic leukemia (CLL), marginal zone lymphoma, follicular lymphoma, and diffuse large B-cell lymphoma. 39 Nonetheless, aberrations in TP53 correlate with an inferior clinical outcome in hematologic cancers.…”
Section: P53 Deregulation In Hematopoietic Tumorsmentioning
confidence: 99%